Implementation of the Honeypot Method in Form Input Security Against Sql-Injection Attacks - Adam Putra; Ade Eviyanti (Procedia of Engineering and Life Science, 2022)
At this time the internet is something that can not be separated in the life of modern society. For this reason, fast, safe and reliable internet is very important. To achieve this on the internet there are various kinds of technology that make it very influential in our lives. In the scope of security for safe and smooth internet web surfing, we need security, especially in the excess part of the website. One way to do this is to commit website crimes, namely Sql Injection. Sql injection is a hacking action that is carried out in the client application by modifying the SQL commands that are in the client application memory. SQL Injection is a technique for exploiting web applications, commands can be entered as desired by the user even though the user is not authorized to do so. The damage done by the user that can lead to fatal consequences can be done by using SQL injection. One of the methods used to prevent website security attacks is Honeypot. Honeypot is a system or computer that is deliberately used as bait to become a target for attacks from attackers.